2007
DOI: 10.1097/01.sap.0000253745.07940.da
|View full text |Cite
|
Sign up to set email alerts
|

Penile Reconstruction by the Free Scapular Flap and Malleable Penis Prosthesis

Abstract: : The scapular free flap is an ideal flap that achieves satisfactory function and esthetic appearance for penile reconstruction because of its adequate amount of tissue, reliable vascularity, acceptable donor-site morbidity, and reliable blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
0
29
0
3
Order By: Relevance
“…11 The vascular pattern is predictable and there is sufficient tissue bulk to create a neophallus. 2,8,12 Questions regarding donor morbidity related to radial fracture following osteocutaneous flap harvest and bone viability after transfer have been answered. [13][14][15] Cosmesis in total penile reconstruction has not been emphasized in the literature perhaps due to its inherent complexity in transfer and satisfaction with obtaining a functional reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The vascular pattern is predictable and there is sufficient tissue bulk to create a neophallus. 2,8,12 Questions regarding donor morbidity related to radial fracture following osteocutaneous flap harvest and bone viability after transfer have been answered. [13][14][15] Cosmesis in total penile reconstruction has not been emphasized in the literature perhaps due to its inherent complexity in transfer and satisfaction with obtaining a functional reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Total penile reconstruction has been successfully performed with the use of pedicled and free tissue transfers. [1][2][3][4][5][6][7] Attempts have been made to more clearly identify the distinction between the penile shaft and the glans penis in the reconstruction, however, this cosmetic endeavor is an area of ongoing innovation. 8…”
mentioning
confidence: 99%
“…Rohrich et al () described the use of a latissimus dorsi free flap, in combination with a free scapula skin flap, for simultaneous penile and perineal reconstruction. However, it was not until 2007 that Wang et al () and Yang et al () reported the utilization of the free scapular skin flap. Both studies reported favorable results.…”
Section: Evolution Of Female‐to‐male Transgender Genital Reconstructionmentioning
confidence: 99%
“…He recommended this flap as an ideal flap that achieves satisfactory function and appearance for penile reconstruction because of its adequate amount of tissue, acceptable donor-site morbidity and reliable blood supply. [51]…”
Section: Phalloplasty Techniquesmentioning
confidence: 99%